Hypertrophic cardiomyopathy: Cardiac structural and microvascular abnormalities as evaluated with multi-parametric MRI. Issue 8 (August 2015) - Zhang, Yu-Dong; Li, Meijiao; Qi, Liang; Wu, Chen-Jiang; Wang, Xiaoying
Highlights: LGE-present HCM had lower K trans, higher V e and MTT against LGE-absent HCM and normal group. LGE-absent had significantly higher V e and MTT against normal group. K trans was not changed between LGE-absent and normal group Microcirculatory dysfunction in HCM closely correlated to structural abnormality. Abstract: Purpose: To determine the relationship between myocardial structural and microvascular abnormality in hypertrophic cardiomyopathy (HCM) by multi-parametric cardiac MRI. Materials and methods: Twenty-four HCM and eighteen controls were retrospectively included. Left ventricle mass (LVM), LV end-systolic and end-diastolic volume (LVESV, LVEDV), LV ejection fraction (LVEF), and 16-segment wall thickness at ES and ED (SESWT, SEDWT) were assessed with a 2D cine-MRI. Myocardial perfusion (reflected by K trans ), interstitial volume ( V e ) and mean transmit time (MTT) were evaluated with a model-dependent dynamic contrast-enhanced MRI. Myocardial fibrosis was assessed with late gadolinium enhancement (LGE) imaging. Results: K trans was significantly decreased in LGE-present (0.74 ± 0.15 mL/g/min) against LGE-absent (0.55 ± 0.14 mL/g/min, p = 0.030) and normal group (0.81 ± 0.32 mL/g/min, p < 0.001), but was unchanged in LGE-absent against normal group ( p > 0.05). V e and MTT were significantly increased in LGE-present ( V e : 26.7 ± 15.7%; MTT: 28.6 ± 21.3 s) against LGE-absent (37.6 ± 18.3%; 49.8 ± 30.5 s) and normal group (19.7 ± 6.9%; 15.1 ± 3.9 s; all p < 0.001), and were significantly increased in LGE-absent against normal group ( p < 0.001). LGE significantly correlated to K trans, V e, MTT, and SESWT ( ρ = 0.232, −0.247, −0.443, and −0.207, respectively). K trans negatively correlated to SEDWT and SESWT ( ρ = −0.224 and −0.231). V e and MTT positively correlated to SEDWT ( V e : ρ = 0.223; MTT: ρ = 0.239) and SESWT ( V e : ρ = 0.248; MTT: ρ = 0.254). Conclusions: Consistent relationship was determined between myocardial structural abnormality and microvascular dysfunction in HCM.